Shining a Light: Examining Similarities and Differences in the Work Psychology of Health Support Workers Employed in Long-Term Care and Home and Community Care Settings. (November 2019) - Perreira, Tyrone A.; Berta, Whitney; Laporte, Audrey; Ginsburg, Liane; Deber, Raisa; Elliott, Gillian; Lum, Janet
Health Support Workers (HSWs) provide up to 80% of care to residents and clients in the long-term care (LTC) and home and community care (HCC) sectors but have received little research attention compared with the regulated professions. The authors explore similarities and differences in the work psychology of HSWs employed in LTC and HCC settings. Data were collected via survey from 276 LTC and 184 HCC HSWs. Descriptive statistics and path analyses were conducted. HSWs in LTC and HCC settings have significant, positive associations between organizational citizenship behaviors directed toward the organization (OCB-Os) and psychological empowerment, as well as intention to stay (ITS) and job satisfaction. For LTC sector HSWs, there are significant relationships between OCB-Os and quality of work life (QWL), ITS and work engagement, and individual performance and both job satisfaction and QWL. For the HCC sector, OCB-Os and ITS are significantly and directly related to organizational commitment. This study has implications for organizations interested in developing targeted interventions to improve the retention of HSWs.